2021
DOI: 10.3390/nu13020634
|View full text |Cite
|
Sign up to set email alerts
|

Protein Intake and Physical Activity in Newly Diagnosed Patients with Acute Coronary Syndrome: A 5-Year Longitudinal Study

Abstract: Cardiovascular disease is one of the most common causes of hospitalization and is associated with high morbidity and mortality rates. Among the most important modifiable and well-known risk factors are an unhealthy diet and sedentary lifestyle. Nevertheless, adherence to healthy lifestyle regimes is poor. The present study examined longitudinal trajectories (pre-event, 6-, 12-, 24-, 36-, and 60-month follow-ups) of protein intake (fish, legumes, red/processed meat) and physical activity in 275 newly-diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
(97 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, since the duration of hospitalization is being reduced and the attention is more focused on the resolution of the acute problem, CR responds to the need to implement other types of intervention, such as health education and information, promotion of lifestyle changes, monitored physical activity, therapeutic optimization, risk stratification, functional and global evaluation [ 1 ]. CR health education interventions are particularly of interest to improve awareness of CV risk factors [ 2 ] and adherence to medical therapies [ 3 ]. CR participation after an ACS has demonstrated to be effective in reducing subsequent mortality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since the duration of hospitalization is being reduced and the attention is more focused on the resolution of the acute problem, CR responds to the need to implement other types of intervention, such as health education and information, promotion of lifestyle changes, monitored physical activity, therapeutic optimization, risk stratification, functional and global evaluation [ 1 ]. CR health education interventions are particularly of interest to improve awareness of CV risk factors [ 2 ] and adherence to medical therapies [ 3 ]. CR participation after an ACS has demonstrated to be effective in reducing subsequent mortality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, in our study, we found that the hospitalisation rate for IHDs was higher among males compared to females for most types of IHDs. This could be attributed to their lifestyle, including physical inactivity and poor diet [ 25 ]. At the same time, there are other risk factors (psychosocial risk factors) that affect the traditional risk factors and increase males’ risk of developing CVDs and its associated complications that could lead ultimately to the need for urgent medical assistance and hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…While doctors treat patients in hospital continued care at home is self-dependent ( 7 ), requiring that doctors and patients develop a shared understanding of the disease process and treatment goals to prevent a breakdown in management ( 5 7 ). It is worth noting however that compliance with health-related lifestyle changes may wane from about six months after institution, resulting in poorer compliance with the proposed changes ( 8 ).…”
Section: Discussionmentioning
confidence: 99%